Adaptive Aspects of Hominization. Part I. Morphological and Physiological Adaptations - Kujawa, Betina (Anthropological Review, 1993)
Both some geological, climatic and material traces that are used in paleonthology let reconstruct the complex of the adaptive traits that were developed in Australopithecines. The environmental conditions of the South-Eastern Africa in late Pliocene and early Pleistocene directed some morphological, physiological and behavioural changes which the first hominids underwent.